ASPECTS OF THE RELATIONSHIP BETWEEN FIXED DENTAL PROSTHESES AND PERIODONTAL TISSUES - Alina Dimofte; Lucian-Paul Dragomir; Mihai-Raul Popescu; Dora-Maria Popescu; Dorin-Nicolae Gheorghe; Maria-Alexandra Martu; Petra Surlin (Romanian Dental Association for Education, 2021)
The health of periodontal tissues is the key to the long-term success of prosthetic restorations. A negative impact on it can have subgingival margins, an inaccurate marginal fit, materials that favor the accumulation of plaque and can suffer the corrosion process. All these characteristics can stimulate the appearance of a biological response, that can be translated by increased proinflammatory markers (interleukins, matrix metalloproteinases) in gingival crevicular fluid. The acquisition of the aspects that describe the relationship between the two elements mentioned above, could ensure a favorable prognosis of fixed prosthetic therapy.